Question
upstudy study bank question image url

\begin{tabular}{|c|c|}\hline\( g(x)=\frac{1}{5 x^{3}} \) & \( h(x)=x^{2}|x|+4 \) \\ Even & Even \\ Odd & Odd \\ Neither & Neither \\ \hline\end{tabular}

Ask by May Dunn. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( g(x) \) is Odd and \( h(x) \) is Even.

Solution

Function by following steps: - step0: Determine if even, odd or neither: \(h\left(x\right)=x^{2}\left|x\right|+4\) - step1: Use substitution: \(h\left(-x\right)=\left(-x\right)^{2}\left|-x\right|+4\) - step2: Simplify: \(h\left(-x\right)=x^{2}\left|x\right|+4\) - step3: Use substitution: \(h\left(-x\right)=h\left(x\right)\) - step4: The function is an even function: \(\textrm{Even}\) Determine whether the function \( g(x)=\frac{1}{5 x^{3}} \) is even or odd Function by following steps: - step0: Determine if even, odd or neither: \(g\left(x\right)=\frac{1}{5x^{3}}\) - step1: Use substitution: \(g\left(-x\right)=\frac{1}{5\left(-x\right)^{3}}\) - step2: Simplify: \(g\left(-x\right)=-\frac{1}{5x^{3}}\) - step3: Use substitution: \(g\left(-x\right)=-g\left(x\right)\) - step4: The function is an odd function: \(\textrm{Odd}\) Let's analyze the functions \( g(x) \) and \( h(x) \) to determine their properties regarding being even, odd, or neither. 1. **Function \( g(x) = \frac{1}{5 x^{3}} \)**: - After analysis, we find that \( g(x) \) is **Odd**. This means that \( g(-x) = -g(x) \) for all \( x \) in the domain of \( g \). 2. **Function \( h(x) = x^{2}|x| + 4 \)**: - After analysis, we find that \( h(x) \) is **Even**. This means that \( h(-x) = h(x) \) for all \( x \) in the domain of \( h \). ### Summary: - \( g(x) = \frac{1}{5 x^{3}} \) is **Odd**. - \( h(x) = x^{2}|x| + 4 \) is **Even**.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To determine if the functions \( g(x) \) and \( h(x) \) are even, odd, or neither, let's analyze each one. For \( g(x) = \frac{1}{5 x^{3}} \), plugging in \(-x\) gives \( g(-x) = \frac{1}{5 (-x)^{3}} = -\frac{1}{5 x^{3}} = -g(x) \). Hence, \( g(x) \) is an odd function. For \( h(x) = x^{2}|x| + 4 \), we substitute \(-x\) to get \( h(-x) = (-x)^{2}|-x| + 4 = x^{2}(-x) + 4 = x^{2}|-x| + 4 = x^{2}|x| + 4 = h(x) \). Thus, \( h(x) \) is an even function. So, \( g(x) \) is odd and \( h(x) \) is even!

Related Questions

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy